Irrational exuberance - Shiller, Robert J. (Princeton, NJ. Princeton University Press, 2015)
"In this revised, updated, and expanded edition of his New York Times bestseller, Nobel Prize-winning economist Robert Shiller, who warned of both the tech and housing bubbles, now cautions that signs of irrational exuberance among investors have only increased since the 2008-9 financial crisis. With high stock and bond prices in the United States, and rising housing prices in many countries, the post-subprime boom may well turn out to be another illustration of Shiller's influential argument that psychologically driven volatility is an inherent characteristic of all asset markets. In other words, Irrational Exuberance is as relevant as ever. But Irrational Exuberance is about something far more important than the current situation in any given market because the book explains the forces that move all markets up and down. It shows how investor euphoria can drive asset prices up to dizzying and unsustainable heights, and how, at other times, investor discouragement can push prices down to very low levels. Previous editions covered the stock and housing markets--and famously predicted their crashes. This new edition expands its coverage to include the bond market, so that the book now addresses all of the major investment markets. This edition also includes updated data throughout, as well as Shiller's 2013 Nobel Prize lecture, which puts the book in broader context. In addition to diagnosing the causes of asset bubbles, Irrational Exuberance recommends urgent policy changes to lessen their likelihood and severity--and suggests ways that individuals can decrease their risk before the next bubble bursts. No one whose future depends on a retirement account, a house, or other investments can afford not to read it"--Provided by publisher.
Preface to the third edition -- Preface to the second edition, 2005 -- Preface to the first edition, 2000 -- The stock market in historical perspective -- The bond market in historical perspective -- The real estate market in historical perspective -- Structural factors. Precipitating factors : the Internet, the capitalist explosion, and other events ; Amplification mechanisms : naturally occurring Ponzi processes -- Cultural factors. The news media ; New era economic thinking ; New eras and bubbles around the world -- Psychological factors. Psychological anchors for the market ; Herd behavior and epidemics -- Attempts to rationalize exuberance. Efficient markets, random walks, and bubbles ; Investor learning and unlearning -- A call to action. Speculative volatility in a free society -- Appendix. Nobel Prize lecture : Speculative asset prices.
Includes bibliographical references (pages 321-338) and index.
Keywords: Stocks -- United States; Stock exchanges -- United States; Stocks -- Prices -- United States; Real property -- Prices -- United States; Risk; Dow Jones industrial average